Multicultural Education: Fostering Diversity and Inclusion in the Classroom Environment - Wulandari Wulandari (Education Studies and Teaching Journal (EDUTECH), 2024)
Multicultural education has an important role in promoting cultural diversity and educational equality. This article highlights some effective multicultural teaching strategies, such as cooperative approaches, project-based learning, and problem-based learning. Teachers play a key role in implementing this strategy by understanding students' culture and applying it contextually. However, Indonesia is faced with challenges such as lack of teacher knowledge and skills, lack of institutional support, and teacher readiness to teach in multicultural classes. This article also identifies limitations in this research, including theoretical sources, general scope of discussion, and a lack of understanding of indicators of successful implementation of multicultural strategies. Furthermore, a further research agenda is recommended to deepen understanding of multicultural teaching strategies in Indonesia, including implementation trials, development of assessment instruments, and classroom action research.